Common interests in the international space of Antarctica - Berkman, Paul Arthur (Polar Record, 2009)
The Antarctic Treaty was adopted by twelve nations in Washington, DC on 1 December 1959 with the interests of science and the progress of all mankind. Seven of these nations asserted territorial claims, including the overlapping claims of Argentina, Chile and the United Kingdom in the Antarctic Peninsula. The five other nations were non-claimants, including the United States and Soviet Union (now Russian Federation), which reserved rights to press claims in the future.